Psychosocial and occupational predictors of health among Spanish University Employees: The role of job type, contract status, and seniority - Ángela Asensio-Martínez; Alejandra Aguilar-Latorre; Barbara Masluk; Sandra León-Herrera; Raquel Sánchez Recio; Bárbara Oliván-Blázquez (PLoS ONE, 2026)
The digital transformation of work environments, particularly in academia, has introduced new psychosocial risks, including technostress. This cross-sectional study analyses the relationship between technostress and general health among university employees at the University of Zaragoza, examining the moderating effects of job type, contract status, and seniority. A total of 458 staff members, including academic and research staff and administrative and service staff, completed an online survey assessing general health, technostress, perceived stress, burnout, job satisfaction, resilience, social support, and other occupational variables. The results revealed that perceived stress was the most consistent predictor of emotional symptomatology across all subgroups. Technostress also emerged as a significant predictor, especially among permanent employees and those with longer tenure. Conversely, resilience and job satisfaction functioned as protective factors. Differences in health outcomes were observed depending on employment conditions, highlighting the importance of organizational context. These findings underscore the need for tailored interventions to mitigate psychosocial risks associated with information and communication technologies use and to enhance well-being in academic institutions. This study contributes to the growing evidence base on the health implications of digital work environments in the higher education sector.